Rumble Tum - Peters, Stephanie True, 1965-; Papp, Robert (New York : Dutton Children's Books, 2009)
With help from her brother and parents, Beth takes very good care of her new kitten, Rumble Tum, but when she closes her eyes for a moment one stormy day, her beloved pet disappears.
2.2
K-3
Keywords: Kittens -- Juvenile fiction; Families -- Juvenile fiction; Cats -- Fiction; Animals -- Infancy -- Fiction; Family life -- Fiction; Lost articles -- Fiction; Cats -- Fiction; Animal babies -- Fiction; Family life -- Fiction; Lost and found possessions -- Fiction; Picture books for children